Market research for food products and processes in developing countries : proceedings of a workshop held in Singapore, 1-4 April 1986 - Young, R H., ed. (IDRC OttawaCA, 1987)
Creates a greater awareness of opportunities for using market research in guiding food technology projects in developing countries and highlights market research methodologies that were appropriate for use by Asian scientists. Provides case study examples demonstrating market research in food technology projects along with conclusions and recommendations of participants on ways to increase use of this type of analysis in future research.